Political Culture, Socio-Cultural Values and Democratic Consolidation in Croatia - Matić, Davorka (Array, 2008)
The article analyzes the current state of democracy in Croatia. Building on theories of democratic consolidation the author attributes the slow pace of democratization in Croatia to the pressing tasks of state-building and state- securing sfforts prior ro rhe full incorporation of Croatian territory to Zagreb's control in 1998. Since the death of Tuđman, the pace of reform has stepped up and Croatia is today a stable conslidated democracy. Still, the analysis concludes that the quality of Croatian democracy still leaves much to be desired, and polling data show that the public has a very low trust in the country's key institutions and are disappointed witht the functioning or output of democracy.